Evaluation of Cortical Thicknesses and Bone Density Values of Mandibular Canal Borders and Coronal Site of Alveolar Crest - Emel Tuğba Ataman-Duruel; Zehra Beycioğlu; Doğukan Yılmaz; Samir Goyushov; Tansu Çimen; Onurcem Duruel; Hasan Güney Yılmaz; Tolga Fikret Tözüm (eJournal of Oral Maxillofacial Research)
Objectives: The objectives of this retrospective study are to measure the amount of the alveolar crest cortication and cortication around the mandibular canal, and to evaluate bone density values of alveolar crest, cortication around mandibular canal, and possible implant placement area for edentulous sites.